Intense Red-Emitting Upconversion Nanophosphors (800 nm-Driven) with a Core/Double-Shell Structure for Dual-Modal Upconversion Luminescence and Magnetic Resonance in Vivo Imaging Applications - Hong, A-Ra; Kim, Youngsun; Lee, Tae Sup; Kim, Sehoon; Lee, Kwangyeol; Kim, Gayoung; Jang, Ho Seong (American Chemical Society, 2018)
In this study, intense single-band red-emitting upconversion nanophosphors (UCNPs) excited with 800 nm near-infrared (NIR) light are reported. When a NaYF4:Nd,Yb active-shell is formed on the 12.7 nm sized NaGdF4:Yb,Ho,Ce UCNP core, the core/shell (C/S) UCNPs show tunable emission from green to red, depending on the Ce3+ concentration under excitation with 800 nm NIR light. Ce(3+)doped C/S UCNPs (30 mol %) exhibit single-band red emission peaking at 644 nm via a F-5(5) -> I-5(8) transition of Ho3+. A high Nd3+ concentration in the shell results in strong absorption at around 800 nm NIR light, even though the shell thickness is not large, and small-sized C/S UCNPs (16.3 nm) emit bright red light under 800 nm excitation. The formation of a thin NaGdF4 shell on the C/S UCNPs further enhances the upconversion (UC) luminescence and sub-20 nm sized core/double-shell (C/D-S) UCNPs exhibit 2.8 times stronger UC luminescence compared with C/S UCNPs. Owing to the strong UC luminescence intensity and Gd3+ ions on the surface of nanocrystals, they can be applied as a UC luminescence imaging agent and a T-1 contrast agent for magnetic resonance (MR) imaging. In vivo UC luminescence and high-contrast MR images are successfully obtained by utilizing the red-emitting C/D-S UCNPs.
Keywords: FACILE SYNTHESIS; NANOCRYSTALS; NANOPARTICLES; THERAPY; DESIGN; PROBES